ANALISIS KEMAMPUAN PENYELESAIAN MASALAH DAN KOMUNIKASI MATEMATIS SOAL INSTRUMEN RELASI DAN FUNGSI PADA SISWA KELAS IX DI KABUPATEN BANDUNG - Bakti Pertiwi; Chandra Novtiar (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is a qualitative descriptive study that aims to analyze the ability of problem solving and mathematical communication through the results of the answers to the descriptions done by students. The instrument used is 6 items about the description of relation and function material. The subjects of this study were 15 grade IX students from various junior high schools in Bandung district. The form of data collection is a study of the results of the answers to student descriptions which are described in accordance with the selected indicators of problem solving abilities and mathematical communication. Based on the results of the analysis of problem solving abilities with indicators identifying elements that are known, asked, and the adequacy of the elements needed by 78%, formulating mathematical problems 68.3%, applying strategies to solve problems 84.7%, interpreting the results of problem solving 61% . While the results of the analysis of mathematical communication indicators explain mathematical ideas, situations, and mathematical relations orally or in writing with real objects diagrams, pictures, graphs and algebra by 78%, stating daily events in mathematical language 60%. Based on the results of the analysis of mathematical problem solving and communication skills, Grade nineÂ  junior high school students in Bandung district were classified as moderate.